2008
DOI: 10.1101/lm.893808
|View full text |Cite
|
Sign up to set email alerts
|

L-type voltage-gated calcium channels in conditioned fear: A genetic and pharmacological analysis

Abstract: Using pharmacological approaches, others have suggested that L-type voltage-gated calcium channels (L-VGCCs) mediate both consolidation and extinction of conditioned fear. In the absence of L-VGCC isoform-specific antagonists, we have begun to investigate the subtype-specific role of LVGCCs in consolidation and extinction of conditioned fear using a molecular genetics approach. Previously, we used this approach to demonstrate that the Ca v 1.3 isoform mediates consolidation, but not extinction, of contextually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
6
42
0
Order By: Relevance
“…Next, Waltereit et al (2008) examine locomotor activity and rearing behavior in mice injected with nifedipine. In agreement with the findings of McKinney et al (2008) and Busquet et al (2008), they observe decreases in locomotor activity and a complete loss of rearing behavior that lasts up to 4 h after s.c. administration of nifedipine. Further, both i.p.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Next, Waltereit et al (2008) examine locomotor activity and rearing behavior in mice injected with nifedipine. In agreement with the findings of McKinney et al (2008) and Busquet et al (2008), they observe decreases in locomotor activity and a complete loss of rearing behavior that lasts up to 4 h after s.c. administration of nifedipine. Further, both i.p.…”
supporting
confidence: 90%
“…However, in that study, deletion of Ca v 1.3 had no effect on fear extinction; Ca v 1.3 knockout mice show normal within-session extinction and intact long-term recall of extinction 24 h later (McKinney and Murphy 2006). In the present article, McKinney et al (2008) examine the role of Ca v 1.2 in fear memory extinction. A recent study found that deletion of Ca v 1.2 impairs spatial learning and the L-VGCC-dependent form of LTP in the hippocampus (Moosmang et al 2005).…”
mentioning
confidence: 77%
See 3 more Smart Citations